GENERALIZED СHICKENPOX IN CHILD WITH IMMUNODEFICIENCY - A. L. Rossina; S. B. Chuelov; O. A. Kaschenko; M. V. Popova; O. Y. Brunova; A. V. Stupina; А. А. Osipov; N. N. Zvereva; Е. V. Novosad; O. B. Kovalev (LLC "Diagnostics and Vaccines", 2017)
The аrticle describes a clinical example of a generalized form of chickenpox  developed in a child with severe background pathology (Sjogren's disease with renal involvement, a secondary immunodeficiency condition), with a common lesion of internal organs, skin and mucous membranes, subsequent attachment of secondary microbial flora and fatal outcome.